Boundary Exponential Gradient Reduced Order Detectability in Neumann Conditions - Al-Bayati, Mrooj A.; Al-Shaya, Ahlam Y.; Al-Saphory, Raheam A. (Iraqi Journal of Science, 2024)
This work, aims to study and examine the description f the gradient reduced order-strategic sensors of type boundary exponential (-strategic sensors) for completion gradient  order-detectability of type boundary exponential (-detectability). Thus, this concept is linked to an estimator in distributed parameter systems (DPSS) in Neumann problem. So,we present numerous consequences regarding to diverse kinds of information, region  and conditions of boundary region to allow existence of -detectable systems. In addition,we have estimated at the junction interface that the interior solution isharmonizedwith the exterior solution for -detectable and, we give the relationship between this concept and sensors structures. Finally,we demonstrate some applications with many circumstances f sensor positions.